2009
DOI: 10.1007/s10826-009-9288-4
|View full text |Cite
|
Sign up to set email alerts
|

Academic Stressors and Anxiety in Children: The Role of Paternal Support

Abstract: We examined the role of paternal support in the relation between academic stress and the mental health of primary school children in Hong Kong. The participants of this cross-sectional study were 1,171 fifth and sixth graders. The results indicated that academic stress was a risk factor that heightened student anxiety levels and that parental emotional support was a protective factor that contributed to better mental health among children. However, paternal informational support delivered to children during ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
68
1
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(84 citation statements)
references
References 47 publications
8
68
1
7
Order By: Relevance
“…The association between academic stress and adolescents' mental health has been discussed in a number of studies (Leung, Yeung, & Wong, 2010). Academic stress is considered one of the most important predictors for adolescents' depression and anxiety.…”
Section: Academic Stress and Mental Healthmentioning
confidence: 99%
See 4 more Smart Citations
“…The association between academic stress and adolescents' mental health has been discussed in a number of studies (Leung, Yeung, & Wong, 2010). Academic stress is considered one of the most important predictors for adolescents' depression and anxiety.…”
Section: Academic Stress and Mental Healthmentioning
confidence: 99%
“…Academic stress is considered one of the most important predictors for adolescents' depression and anxiety. A number of studies have found academic stress to be positively correlated with depression symptoms (Ang & Huan, 2006a;Jayanthi et al, 2015;Lazaratou et al, 2010;Li, 2013;Liu & Lu, 2012) and anxiety symptoms (Ding & Wang, 2003;Leung et al, 2010;Sun, Dunne, Hou, & Xu, 2011;Wen et al, 2010;Xiao, Liang, & He, 2014;Zhuo et al, 2005).…”
Section: Academic Stress and Mental Healthmentioning
confidence: 99%
See 3 more Smart Citations